2020
DOI: 10.1038/s41423-019-0353-7
|View full text |Cite
|
Sign up to set email alerts
|

CD147 deficiency in T cells prevents thymic involution by inhibiting the EMT process in TECs in the presence of TGFβ

Abstract: Thymic involution during aging is a major cause of decreased T-cell production and reduced immunity. Here, we show that the loss of CD147 on T cells prevents thymic senescence, resulting in slowed shrinkage of the thymus with age and increased production of naive T cells. This phenotype is the result of slowing of the epithelial–mesenchymal transition (EMT) process in thymic epithelial cells (TECs), which eventually leads to reduced adipocyte accumulation. In an in vitro coculture system, we found that TGFβ is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 53 publications
(32 reference statements)
1
24
0
Order By: Relevance
“…Yamada et al 20 suggested a role in adherens junction (AJ) formation considering that ANXA2‐silenced MDCK cells were not able to re‐establish AJ during a calcium switch assay. Our finding was re‐enforced by those of Chen et al 21 that also found a relation between TGF‐ß activation and ANXA2‐mediated E‐cadherin internalization during the EMT. ANXA2 might also control TGF‐ß induction of EMT regulating c‐Myc mRNA translation.…”
Section: Figuresupporting
confidence: 87%
“…Yamada et al 20 suggested a role in adherens junction (AJ) formation considering that ANXA2‐silenced MDCK cells were not able to re‐establish AJ during a calcium switch assay. Our finding was re‐enforced by those of Chen et al 21 that also found a relation between TGF‐ß activation and ANXA2‐mediated E‐cadherin internalization during the EMT. ANXA2 might also control TGF‐ß induction of EMT regulating c‐Myc mRNA translation.…”
Section: Figuresupporting
confidence: 87%
“…In EMT, a spindle-like morphology is acquired, cell-cell adhesions are disrupted, and the polarity is changed from apical-basal polarity into front-end-back-end polarity [76,120]. Two proteins known as E-cadherin and N-cadherin are suggested to play a significant role in EMT mechanisms [121,122]. The cadherin proteins shape a cadherin-catenin adhesion complex by attachment into βand α-catenin via their cytoplasmic tails [123].…”
Section: Emt Process In Healthy and Cancerous Tissuesmentioning
confidence: 99%
“…This nanodevice allows for active targeting of either (i) a fluorophore for active tracking or (ii) a drug for monitoring specific cell responses depending on the expression levels of surface proteins. This approach has been successfully validated using two different antibodies that specifically recognize two receptors commonly overexpressed on the cell surface of several types of tumors, the epidermal growth factor receptor (EGFR) 23 and the cluster of differentiation 147 (CD147) 24,25 , and that have been involved in cancer progression and poor prognosis. Additionally, we demonstrate the robust implementation of this nanodevice in cocultures for evaluating the efficacy of cell internalization based on the levels of these receptors.…”
Section: -16mentioning
confidence: 99%